M1. Prueba Corta
M1. Prueba Corta
M1. Prueba Corta
( x 2+ y2 ) dx 2 xydy 0
− =
dx dx dx
( x 2+ y2 ) 2 xydy
− =0
dx dx
( 2 x−c
)
2
(x 2 + ( √ x 2−cx ) )−2 x ( √ x 2−cx ) =0
2 √ x 2−cx
dx 1
=1+
dt √ 1+t 2
ED
x= y ´ + arcsen ( y ´ )
dy
dx dt
y= − …. = t
dt dx
dt
y ´=t
Luego
x= y ´ + ascsen( y ´ )=t
x=x
a) E.D.=?
x x 2 x
y=C 1 e +C 2 x e +C 3 x e
y =C 1 e +C 2 x e +C 2 e +C 3 x e + 2C 3 x e
' x x x 2 x x
y = y +C 2 e +2 C3 x e →C 2 e + 2C 3 x e = y − y
' x x x x '
y = y +C 2 e +2 C3 x e +2 C 3 x e + 2C 3 e
'' ' x x x 3
3
y−x sen x
b. y=x 3 sen ( x ) +C x 3 C= 3
x
´ 3 2 2
y =x cos x +3 x sen x +3 C x
´ 3 3y
y =x cos x +
x
dy 4
x =x cos x−3 y =0
dx